General Journal Recording System Analysis In Companies using Online Accounting Software - Yusup, Muhamad; Padeli, Padeli; Ilamsyah, Ilamsyah (Pandawan, 2017)
A company in its financial activities will certainly make a record that serves to record all types of proof of transactions that will be used in a certain period or commonly referred to as general journals. This is an important activity in the financial part of the company because if the recording of transaction evidence can be done properly, it will be able to provide detailed information about changes in economic resources that occur due to activities carried out by the company in order to gain profits, therefore proof of transaction must stored properly so that when errors occur and errors can be used. By using online accounting software can make it easier to record and analyze general journals and at the same time as a solution to avoid financial manipulation, thus recording general journal activities will be more effective and efficient and safer than still using manual or offline recording. Keywords: ​online accounting software, recording, general journal